Clinical Genetics of Alzheimer's Disease. (13th May 2014) - Zou, Zhangyu; Liu, Changyun; Che, Chunhui; Huang, Huapin
Abstract : Alzheimer's disease (AD) is the most common progressive neurodegenerative disease and the most common form of dementia in the elderly. It is a complex disorder with environmental and genetic components. There are two major types of AD, early onset and the more common late onset. The genetics of early-onset AD are largely understood with mutations in three different genes leading to the disease. In contrast, while susceptibility loci and alleles associated with late-onset AD have been identified using genetic association studies, the genetics of late-onset Alzheimer's disease are not fully understood. Here we review the known genetics of early- and late-onset AD, the clinical features of EOAD according to genotypes, and the clinical implications of the genetics of AD.